2023
DOI: 10.3390/polym15020265
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Bio-Based Attapulgite Copolymer (BAC) Sand-Fixing Material

Abstract: Desertification, one of the world’s most pressing serious environmental problems, poses a serious threat to human survival as well as to social, economic, and political development. Nevertheless, the development of environmentally friendly sand-fixing materials is still a tremendous challenge for preventing desertification. This study developed a bio-based attapulgite copolymer (BAC) by grafting copolymerization of attapulgite, starch, sulfomethyl lignin, and biological mycelia. Water retention, anti-water ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Attapulgite soil is directly added to silty soil; because of its significant gelling characteristics, the dispersed particles can be heavy into larger particle aggregates, the average particle size of soil aggregates is increased, and the water holding performance is improved, which should have a good effect on the development of sandy soil structure, the improvement of water holding and fertilizer retention performance and the reduction of fertilizer nutrient leaching loss [24]. Wang prepared environmentally friendly composite superabsorbent sand fixing materials using the acid modification process from attapulgite soil, which improved the stability of dry aggregates in sandy soil [25]. Luo found that attapulgite slow-release fertilizer can effectively adsorb or distribute soil water and nutrients in the network structure, effectively reducing the leaching loss of water and nutrients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Attapulgite soil is directly added to silty soil; because of its significant gelling characteristics, the dispersed particles can be heavy into larger particle aggregates, the average particle size of soil aggregates is increased, and the water holding performance is improved, which should have a good effect on the development of sandy soil structure, the improvement of water holding and fertilizer retention performance and the reduction of fertilizer nutrient leaching loss [24]. Wang prepared environmentally friendly composite superabsorbent sand fixing materials using the acid modification process from attapulgite soil, which improved the stability of dry aggregates in sandy soil [25]. Luo found that attapulgite slow-release fertilizer can effectively adsorb or distribute soil water and nutrients in the network structure, effectively reducing the leaching loss of water and nutrients [26].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of hydrogel products as sand fixers was investigated with reference to the method of Wang et al and Yuan et al 55,56 To enhance the dispersion of the hydrogel, we thoroughly mixed the hydrogel samples with nine times their mass in water and subjected them to pulverization. Subsequently, we prepared the specimens following the method described in the referenced literature for the initial test (Fig.…”
Section: Sand-fixing Tests Of Pva and Secs-pva Hydrogelsmentioning
confidence: 99%
“…Subsequently, condensation reactions between silanols result in a cross-linked network, thereby eliminating CO 2 emission during the moisture curing process. 18,19 Hyperbranched polymers, owing to their unique spherical and dendritic structures, exhibit low chain entanglement and reduced viscosity, facilitated by numerous functional groups at the chain ends. 20 This effectively compensates for the inherent high viscosity, propensity for gelation, and poor storage stability of polyurethane materials, while imparting enhanced toughness and strength to the adhesives.…”
Section: Introductionmentioning
confidence: 99%